2014
DOI: 10.5194/acp-14-13801-2014
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization of SOA formed from aqueous-phase reactions of phenols with the triplet excited state of carbonyl and hydroxyl radical

Abstract: Abstract. Phenolic compounds, which are emitted in significant amounts from biomass burning, can undergo fast reactions in atmospheric aqueous phases to form secondary organic aerosol (aqSOA). In this study, we investigate the reactions of phenol (compound with formula C6H5OH)), guaiacol (2-methoxyphenol), and syringol (2,6-dimethoxyphenol) with two major aqueous-phase oxidants – the triplet excited states of an aromatic carbonyl (3C*) and hydroxyl radical (· OH). We thoroughly characterize the low-volatility … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
345
3
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(393 citation statements)
references
References 59 publications
44
345
3
1
Order By: Relevance
“…Aqueousphase methylglyoxal reaction products are expected to remain largely in the aerosol phase upon cloud droplet evaporation (Heaton et al, 2009;Loeffler et al, 2006). Syringol (2,6-dimethoxyphenol) and guaiacol (2-methoxyphenol) are also emitted in significant quantities from biomass burning, and previous studies have examined the bulk aqueous-phase photooxidation of syringol and guaiacol (Yu et al, 2014(Yu et al, , 2016, showing production of several CHO compounds that were also observed in the wildfire-influenced cloud water studied here (Table 3). Notably, aqueous SOA formation from phenolic compounds has been shown to enhance light absorption in the UV-visible region (Yu et al, 2014), suggesting that these brown carbon compounds in the cloud water may be important upon cloud droplet evaporation.…”
Section: Canadian Wildfire Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Aqueousphase methylglyoxal reaction products are expected to remain largely in the aerosol phase upon cloud droplet evaporation (Heaton et al, 2009;Loeffler et al, 2006). Syringol (2,6-dimethoxyphenol) and guaiacol (2-methoxyphenol) are also emitted in significant quantities from biomass burning, and previous studies have examined the bulk aqueous-phase photooxidation of syringol and guaiacol (Yu et al, 2014(Yu et al, , 2016, showing production of several CHO compounds that were also observed in the wildfire-influenced cloud water studied here (Table 3). Notably, aqueous SOA formation from phenolic compounds has been shown to enhance light absorption in the UV-visible region (Yu et al, 2014), suggesting that these brown carbon compounds in the cloud water may be important upon cloud droplet evaporation.…”
Section: Canadian Wildfire Influencementioning
confidence: 99%
“…In addition, observations of likely dinitroaromatics during all air mass influences, potentially from aqueous nitration of nitroaromatic compounds, have important implications because of their light-absorbing and mutagenic properties (Purohit and Basu, 2000;Zhang et al, 2011Zhang et al, , 2013. During wildfire influence, the cloud water showed evidence of aqueous SOA formation, including oligomer formation involving methylglyoxal Yasmeen et al, 2010) and aqueousphase reactions of syringol and guaiacol (Yu et al, 2014(Yu et al, , 2016. Monoterpene-derived organosulfates and organonitrates (Surratt et al, 2008) were observed in the cloud water during all air mass influences, similar to previous cloud water studies (Boone et al, 2015;Pratt et al, 2013).…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
“…The coating of BC has been estimated to enhance its absorption by 50-200 %, depending on the relative sizes of the BC core and the coating (Bond et al, 2013). The optical properties of OA can also change due to atmospheric processing, due to aqueous phase reactions, as well as chemical reactions in the organic phase that can lead to the formation of absorbing species (Kitanovski et al, 2014;Yu et al, 2014). Such changes can lead to more scattering or absorption by aerosols and hence modify their direct radiative effect due to the scattering and absorption of incoming solar radiation.…”
Section: Par1culate Ma4ermentioning
confidence: 99%
“…A number of ground-based and airborne field studies have found a close correlation between oxalic acid and sulfate in ambient particles and cloud droplets, relating aqueous-phase chemistry to the formation of oxalic acid in aerosols and cloud droplets (Yao et al, 2002(Yao et al, , 2003Yu et al, 2005;Sorooshian et al, 2006Sorooshian et al, , 2007aMiyazaki et al, 2009;Wonaschuetz et al, 2012;Wang et al, 2016). In recent years, several model and laboratory studies have suggested that the aqueous-phase oxidation of highly water-soluble organics like glyoxal, methylglyoxal and glyoxylic acid can efficiently produce oxalic acid in aerosol particles and cloud droplets (Lim et al, 2010;Myriokefalitakis et al, 2011;Ervens et al, 2014;Yu et al, 2014;McNeill, 2015). Recent stable carbon isotope studies and field observations have also suggested that oxalic acid forms through aqueous-phase reactions (Wang et al, 2012;Cheng et al, 2015).…”
mentioning
confidence: 99%